Characterizing the semantic and form-based similarity spaces of the mental lexicon by means of the multi-arrangement method - Ansteeg, Lukas; Leoné, Frank; Dijkstra, Ton (Frontiers in Psychology, 2022)
Collecting human similarity judgements is instrumental to measuring and modeling neurocognitive representations (e.g., through representational similarity analysis) and has been made more efficient by the multi-arrangement task. While this task has been tested for collecting semantic similarity judgements, it is unclear whether it also lends itself to phonological and orthographic similarity judgements of words. We have extended the task to include these lexical modalities and compared the results between modalities and against computational models. We find that similarity judgements can be collected for all three modalities, although word forms were considered more difficult to sort and resulted in less consistent inter- and intra-rater agreement than semantics. For all three modalities we can construct stable group-level representational similarity matrices. However, these do not capture significant idiosyncratic similarity information unique to each participant. We discuss what the potential underlying causes are of the differences between modalities and the effect on the application of the multi-arrangement task.